2020
DOI: 10.1017/s1368980019004439
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition status in adult Chilean population: economic, ethnic and sex inequalities in a post-transitional country

Abstract: Objective: To assess the relationship between malnutrition, socioeconomic status (SES) and ethnicity in Chilean adult population. Design: Nationally representative survey (ENS) conducted in 2016–2017. Sociodemographic information, weight, height and hemoglobin (Hb) were measured (2003 ENS). Excess weight was defined as BMI ≥25 kg/m2. Undernutrition included underweight (BMI <18·5 kg/m2), short stature (height <1·49 m in women and <1·62 m in men) or anaemia (Hb <12 g/l). Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…Chile ranks second in the OECD (Organization for Economic Co-operation and Development) list of countries with higher obesity rates, with a prevalence of 13.1% in 6-7 years school children and 30.5 and 38.8% in adult men and women (from 20 to 49 years), respectively (1,2). This is an important finding considering that high body mass index and diet-associated risk factors are currently considered as the leading cause of premature death and disability in the world, including in children (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Chile ranks second in the OECD (Organization for Economic Co-operation and Development) list of countries with higher obesity rates, with a prevalence of 13.1% in 6-7 years school children and 30.5 and 38.8% in adult men and women (from 20 to 49 years), respectively (1,2). This is an important finding considering that high body mass index and diet-associated risk factors are currently considered as the leading cause of premature death and disability in the world, including in children (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…These could be involved in the differences observed. Although it is not ruled out that, during the last decades, Chile has faced an extremely rapid nutritional transition (36), which is congruent with the rapid economic growth observed between 1980 and 2014 (37), it is currently characterized as a post-transitional country, where the nutritional status of the population varies significantly according to sex, socioeconomic level and ethnicity (38).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that not only diseases, but also multiple factors, such as ethnicity, socioeconomic, even the education level of parents and the feeding behavior can effect growth and development status of children [21][22][23][24] . Thus, the cause and intervention for growth retardation may varied among different countries.…”
Section: Retardation Patternmentioning
confidence: 99%